Technical Digest. CLEO/Pacific Rim '99. Pacific Rim Conference on Lasers and Electro-Optics (Cat. No.99TH8464)
DOI: 10.1109/cleopr.1999.814783
|View full text |Cite
|
Sign up to set email alerts
|

Low threshold GaInAsP lasers with semiconductor/air DBR fabricated by inductively coupled plasma etching

Abstract: For GaInAsPDnP lasers used in access networks, low cost, simple process, and integration with other devices, e.g., photodetector and mode-size converter, are required. For this purpose, we have proposed and demonstrated a short cavity laser with semiconductor/air DBRs [l]. So far, this DBR has been fabricated by an ECR RIBE[ 13 and an anisotropic wet etching [2]. However, the reflectivity was reduced by the sidewall tilt, roughness and the diffraction of light in the air region. In this study, we fabricated hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The lateral light is not extracted from a simple diluted semiconductor, while it is extracted from the microcolumns. In another study concerning a laser diode with a deep grating DBR, we carried out a finite difference time-domain simulation of light in a periodic structure of semiconductor vertical walls and air space, which has a similar side view to that of the formed columns [21]. We observed that the transmission of the lateral light through the grating was dependent on the design, e.g., the first-and the second-order grating conditions.…”
Section: Light Extraction Efficiencymentioning
confidence: 99%
“…The lateral light is not extracted from a simple diluted semiconductor, while it is extracted from the microcolumns. In another study concerning a laser diode with a deep grating DBR, we carried out a finite difference time-domain simulation of light in a periodic structure of semiconductor vertical walls and air space, which has a similar side view to that of the formed columns [21]. We observed that the transmission of the lateral light through the grating was dependent on the design, e.g., the first-and the second-order grating conditions.…”
Section: Light Extraction Efficiencymentioning
confidence: 99%